The Effectiveness of Positive Thinking Training on Childbirth Fear and Childbirth Self-efficacy in Pregnant Women in Sari - Emadian, Seyedeh Olia (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this study was to investigate the effectiveness of positive thinking training on childbirth fear, and childbirth self-efficacy in primiparous pregnant women in Sari. Methods: The present research method was semi-experimental with a pre-test-post-test design with a control group and a follow-up period. The statistical population of this study will be all primiparous pregnant women in Sari in autumn of 98. The sample included 30 pregnant women (15 for the control group and 15 for the experimental group) who were selected by non-random sampling. Data collection tools were unconditional acceptance questionnaire and cognitive-emotional adjustment questionnaire. Data analysis was performed using spss software version 26. In this study, to analyze the data, to investigate all the hypotheses and to determine the impact of intervention on the experimental group and to evaluate the difference between the two groups in the pre-test and post-test intervals, first use KS to normalize the data and then analyze Analysis of covariance (ANCOVA) was used. Results: The results of this study indicate that the training of positive thinking intelligence training has a positive effect on fear of childbirth (F=109.25, P=0.001) and childbirth self-efficacy (F=80.19, P=0.001) in primiparous women. Conclusion: According to the results of the research, it can be said that positive thinking training is an effective treatment for the fear of childbirth and childbirth self-efficacy in pregnant women, which can be used by psychologists and counselors.